2021
DOI: 10.1021/acs.est.0c06712
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Toxicologically Significant Compounds in Urban Wildfire Ash Using In Vitro Bioassays and High-Resolution Mass Spectrometry

Abstract: Urban wildfires may generate numerous unidentified chemicals of toxicity concern. Ash samples were collected from burned residences and from an undeveloped upwind reference site, following the Tubbs fire in Sonoma County, California. The solvent extracts of ash samples were analyzed using GC– and LC–high-resolution mass spectrometry (HRMS) and using a suite of in vitro bioassays for their bioactivity toward nuclear receptors [aryl hydrocarbon receptor (AhR), estrogen receptor (ER), and androgen receptor (AR)],… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
(70 reference statements)
1
9
0
Order By: Relevance
“…Our experiment showed that PMFF increased the mRNA expression of IL-6, IL-8, TNF-α, and COX-2 in the treated cells. Consistent with the results of previous studies, PM from wildfire and wood smoke emissions produced high levels of IL-6, IL-8, TNF-α, and COX-2 both in vitro and in vivo [71][72][73]. Our results also demonstrated that RA-RF, a natural polyphenol component found in perilla, reduced IL-6, IL-8, TNF-α, and COX-2 gene expression.…”
Section: Discussionsupporting
confidence: 92%
“…Our experiment showed that PMFF increased the mRNA expression of IL-6, IL-8, TNF-α, and COX-2 in the treated cells. Consistent with the results of previous studies, PM from wildfire and wood smoke emissions produced high levels of IL-6, IL-8, TNF-α, and COX-2 both in vitro and in vivo [71][72][73]. Our results also demonstrated that RA-RF, a natural polyphenol component found in perilla, reduced IL-6, IL-8, TNF-α, and COX-2 gene expression.…”
Section: Discussionsupporting
confidence: 92%
“…In recent years studies have shown that the AhR acts as an environmental sensor of environmental pollutants such as ambient air particulate matter (PM) modifying the immune response ( Vogel et al, 2020 ). Especially, PM collected from TRAP and wildfires have been found to activate the AhR pathway and induce CYP1A1 as well as inflammatory cytokines ( Castañeda et al, 2018 ; Young et al, 2021 ; O'Driscoll et al, 2018 ). Here we tested the effects of TRAP-derived PM collected in a tunnel system near San Francisco (CA) before and during a firestorm in 2017 and a PM sample collected from the Carr wildfire in Redding (CA) on the expression of IL-22 in BMM ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, the exposure to endogenous ligands like FICZ or the prototypical ligand TCDD may totally depend upon AhR, environmentally abundant AhR ligands in mixtures such as PM containing PAHs and metals may involve additional pathways including NF-κB to dysregulate the expression of cytokines like IL-22. Recently, we were able to identify components in wildfire ash samples which correlated with activation of AhR signaling and the induction of CYP1A1 and IL-8 in macrophages ( Young et al, 2021 ). Wildfire smoke contains numerous hazardous chemicals which may lead to adverse health effects, including potential AhR ligands such as PAHs and dioxin-like chemicals ( Keir et al, 2017 ; Beitel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SRP researchers have developed and used cutting edge tools to detect contaminants in air, water, and soil, during and after a variety of disasters including Hurricane Florence in North and South Carolina [ 46 , 47 , 48 ], Hurricane Maria in Puerto Rico [ 49 , 50 ], and wildfires [ 51 , 52 ]. They have also documented direct and indirect health effects following hurricanes [ 53 , 54 ].…”
Section: Understanding Contaminant Movement In a Changing Climatementioning
confidence: 99%